Ant 4,4, a polyamine-anthracene conjugate, induces cell death and recovery in human promyelogenous leukemia cells (HL-60) - Rui, Traquete; Abdul Ghani, Radiah; Phanstiel, Otto; Heather, Wallace (Springer, 2013)
One of the major problems in cancer therapy is the lack of specificity of chemotherapeutic agents towards cancer cells, resulting in adverse side effects. One means to counter this is to selectively deliver the drug to the cancer cell. Cancer cells accumulate increased concentrations of polyamines compared to normal cells, mainly through an increased uptake of preformed polyamines via the polyamine transport system (PTS). Furthermore, the nonstringent structural requirements of the PTS enable the transport of a range of polyamine-based molecules. Thus, the PTS can be used to transport compounds linked to polyamines selectively to cancer cells. In our laboratory, polyamine–anthracene conjugates have shown potent antitumour activity towards HL-60 cells. The aim of this study was to determine the cytotoxicity of Ant-4,4, a homospermidine–anthracene conjugate, and assess the long-term effects by determining whether cancer cells were able to recover from treatment. During exposure, Ant-4,4 was an effective growth-inhibitory agent in HL-60 cells decreasing viable cell number, protein and polyamine content. Evidence indicates concomitant cell-cycle arrest and increased apoptosis. Once the drug was removed, HL-60 cells recovered gradually over time. Increasing cell number, protein content and polyamine content, as well as diminished effects on cell-cycle and apoptotic stimuli were observed over time. These data suggest that, despite being an effective way of delivering anthracene, these polyamine conjugates do not exert long-lasting effects on HL-60 cells.